Role of Sostdc1 in skeletal biology and cancer - Tong, Xiaoyang; Zhu, Chenyu; Liu, Lifei; Huang, Mei; Xu, Jiake; Chen, Xi; Zou, Jun (Frontiers in Physiology, 2022)
Sclerostin domain-containing protein-1 (Sostdc1) is a member of the sclerostin family and encodes a secreted 28-32 kDa protein with a cystine knot-like domain and two N-linked glycosylation sites. Sostdc1 functions as an antagonist to bone morphogenetic protein (BMP), mediating BMP signaling. It also interacts with LRP6, mediating LRP6 and Wnt signaling, thus regulating cellular proliferation, differentiation, and programmed cell death. Sostdc1 plays various roles skin, intestines, brain, lungs, kidneys, and vasculature. Deletion of Sostdc1 gene in mice resulted in supernumerary teeth and improved the loss of renal function of Alport syndrome. In the skeletal system, Sostdc1 is essential for bone metabolism, bone density maintenance, and fracture healing. Recently, Sostdc1 has been found closely related to the development and progression of multiple cancer types, including breast, renal, gastric, and thyroid cancers. This article summarises the role of Sostdc1 in skeletal biology and related cancers to provide a theoretical basis for the treatment of related diseases.